THE APPLICATION OF PSYCHOANALYTIC COUNSELING IN UNDERSTANDING STUDENTS' POTENTIAL - Habsy, Bakhrudin All; Mulia Putra, Alexander Mario Angger; Laksmana, Tiffada Islamic; Kurnianto , Yovityo Azitya (PT Altin Riset Publishing, 2025)
The purpose of this research is to prove the effectiveness of psychoanalytic counseling in understanding students' potential. The methodology used is a qualitative research method with a type of literature study using analysis of relevant literature as the main source of information. The findings discussed in this article are the definition of psychoanalytic counseling, the purpose of psychoanalytic counseling, psychoanalytic counseling techniques, the stages of psychoanalytic counseling techniques, the definition of self-potential, types of self-potential, and the application of psychoanalytic counseling in dealing with self-potential.